Standardizing drying methods and evaluation of the biochemical composition of the fresh and dried "Bhat masali" - Tanushree Sardar; Amjad K. Balange; K.A. Martin Xavier; Binaya Bhusan Nayak; Manjusha L. (Journal of Indian Fisheries Association, 2022)
The present study was conducted to select the ideal drying conditions and to evaluate the biochemical composition of bhat masali in terms of quality, hygiene and nutritional purpose. In this study, bhat masali was dried in a mechanical dryer at temperatures 45, 50, and 60°C and by improved sun drying on raised platform. Traditionally sun-dried (control) bhat masali from Nandurbar was brought for comparing with the results of differently dried bhat masali. Based on moisture content, time taken and sensory analysis, standardization of dried bhat masali was done. From the results, among three mechanical drying temperatures (45°C, 50°C, and 60°C) mechanically drying (50°C) was selected. According to sensory scores, control, mechanically dried (50°C), and improved sun-dried bhat masali were more acceptable among the other drying conditions. The yield of mechanically dried bhat masali (50°C) was higher than improved sun-dried bhat masali. The quality parameters of dried bhat masali under different conditions (mechanical drying at 50°C, improved sun-drying, and control) were within the acceptable limit. There was an increase in fat, protein, and ash with the decrease in moisture during mechanical drying (50°C), improved sun drying of bhat masali and control sample. The quality parameters of dried bhat masali were within the acceptable limit. Nutrient profiling (mineral, amino acid, and fatty acid) was also done.